A low‐profile circularly polarized antenna based on a circularly symmetric high impedance surface. Issue 11 (26th July 2021) - Yang, Tian; Ren, Jian; Xi, Rui Qing; Li, Pu Chu; Yin, Ying Zeng
Abstract: A circularly symmetric high impedance surface (HIS)‐based low‐profile circularly polarized antenna with stable phase center is investigated. The antenna consists of a series‐fed eight‐arm spiral slot antenna and a circularly symmetric HIS (CSHIS) used as the ground plane. As the use of CSHIS, the profile of antenna is decease to as low as 0.09 λ ( λ is the free space wavelength), while the phase center of the antenna maintains stable. Also, the gain of the presented antenna is enhanced compared with that utilizing HIS with rectangular unit cell. For verifying, a prototype of the antenna was fabricated and measured. The measured results show that the overlap bandwidth of 3‐dB axial ratio and impedance matching covers 1.14–1.45 GHz (23.9%), and the gain can reach as high as 7.79 dBic. Over the operation band, stable phase center also can be observed.